Non-Take-Up of Social Assistance: Regional Differences and the Role of Social Norms - Hümbelin Oliver (Swiss Journal of Sociology)
This study estimates the prevalence of non-take-up of social assistance using administrative data from the Canton of Bern. Regional variation in non-take-up rates is then used to study the contextual effects of social norms with respect to welfare receipt legitimacy. Social norms are proxied with the degree of urbanity, language regions and communal voter shares of left- and right-wing parties. Multiple regression analysis, extended by several robustness checks, suggests that social norms do indeed have an impact on take-up behavior.